Analysis of the Effect of Stock Prices on Coal Sub- Sector on the Indonesia Stock Exchange 2014-2019 - Rosdiana, Riska (Dinasti Publisher, 2021)
The rise and fall of stock market prices in the capital market is an interesting phenomenon to discuss related to the issue of fluctuations in the value of the company itself. The performance of a company can be seen by looking at the financial statements. To measure the financial statements of a company can use financial ratios in a certain period. This study is to determine the effect of the Current Ratio, Debt To Equity Ratio, and Price Book Value on stock prices. The object of research is the coal sub-sector which is listed on the Indonesia Stock Exchange in 2014-2019. The research design used is causal research. The sampling technique was the purposive sampling method. The population in this study were 25 coal companies listed on the Indonesia Stock Exchange (IDX) in the 2014-2019 period as many as 8 companies met the criteria so that a total of 48 observations were used. The analysis technique used was panel data regression analysis and it was found that the higher model Appropriate use is a random effect. The data used in this study is secondary data. The results of this test indicate that simultaneously (Test F) Current Ratio, Debt to Equity Ratio and Price Book Value have a significant effect on stock prices. Partially (t-test) the Price Book Value variable has a significant positive effect on stock prices and the Debt to Equity Ratio variable has a significant negative effect on stock prices. Only the Current Ratio variable has no significant effect on the share price of coal sub-sector companies on the Indonesia Stock Exchange in 2014 – 2019.